The impact of transition processes on virtual teams’ reflexivity : the role of trust and computer-mediated communication skills - Fernandes, José Nuno Oliveira (2018)
Google has more than 70 offices in 50 countries and Deloitte is distributed through more than a hundred locations around the world, meaning that, probably, at any point in time, members from the same team are working together in disperse geographies. The adoption of virtual teams is growing and are here for the long run (Society for Human Resource Management, 2012) so the purpose of this dissertation is to study the effects of transition processes on virtual teams’ reflexivity through trust and computer-mediated communication (CMC) skills. Data was collected from 200 individuals from real world companies located across the six continents. Results show that transition processes have a statistically significant effect on virtual teams’ reflexivity, and that trust mediates the effect of said relationship. Moreover, results suggest that task-based CMC skills have a statistically significant interaction effect on virtual teams’ reflexivity in low trust-level environments. Interpersonal-based CMC skills, on the other hand, have no statistically significant effect on predicting reflexivity.